Tobacco Consumption and Illegal Drug Use Among Bangladeshi Males: Association and Determinants. (March 2013) - Kabir, M. A.; Goh, Kim-Leng; Khan, M. M. H.
This article aimed to identify the determinants of tobacco consumption and illegal drug use (IDU) as well as to examine the association between these two variables using a representative sample of 3, 771 Bangladeshi males aged 15 to 54 years. Data were collected through Bangladesh Demographic and Health Survey 2007. To identify the determinants, the patterns of tobacco consumption and IDU were analyzed by age, education and occupation, residence, mass media, premarital sex, wealth, and sexually transmitted infections (STIs). Prevalence of smoking cigarette and bidi was roughly 60%. However, the prevalence of IDU was 3.4%, and this proportion is statistically significant ( Z = 11.32, p = .000). After bivariate analysis, almost all variables except STIs were significantly associated with tobacco consumption. Similarly, all variables except residence and mass media were associated with IDU. Based on multivariable adjusted logistic regression analysis, the likelihood of using IDU was approximately twofold (odds ratio [OR] = 1.8, 95% confidence interval [CI] = 1.23-2.53) among bidi smokers and fourfold (OR = 3.8, 95% CI = 2.62-5.56) among cigarette smokers as compared with nonsmokers.